2014
DOI: 10.1039/c4sc00950a
|View full text |Cite
|
Sign up to set email alerts
|

Exploring anion-induced conformational flexibility and molecular switching in a series of heteroaryl-urea receptors

Abstract: Anion-induced conformational switching provides insight into binding selectivity in a series of heteroaryl-urea receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 25 publications
0
23
0
1
Order By: Relevance
“…A follow-up study involving other model compounds provided more evidence for U conformation preference in the case of 1:1 40$HSO 4 À binding, but it also raised uncertainty for the originally assigned binding conformation of 40$Cl À . 18 Proton NMR studies demonstrated the reversibility of the conformational switch modulated by changing the anionic guest from Cl À to HSO 4 À . Another interesting aspect of the chemistry of 40 is selective binding of H 2 PO 4 À , which probably results from hydrogen bonding or even proton transfer between the H 2 PO 4 À proton and the pyridine nitrogen.…”
Section: The Bigger Picturementioning
confidence: 99%
“…A follow-up study involving other model compounds provided more evidence for U conformation preference in the case of 1:1 40$HSO 4 À binding, but it also raised uncertainty for the originally assigned binding conformation of 40$Cl À . 18 Proton NMR studies demonstrated the reversibility of the conformational switch modulated by changing the anionic guest from Cl À to HSO 4 À . Another interesting aspect of the chemistry of 40 is selective binding of H 2 PO 4 À , which probably results from hydrogen bonding or even proton transfer between the H 2 PO 4 À proton and the pyridine nitrogen.…”
Section: The Bigger Picturementioning
confidence: 99%
“…An alternative effect is rotation about the alkyne upon binding of the anion, a conformational change that has also been observed in similar alkyne receptors. 22,23 …”
mentioning
confidence: 99%
“…In the most favorable scenario this strategy would include not only ligands that are functionalized with the highest possible number of hydrogen bonding sites, but also those that are preorganized in conformations readily positioned for binding a tetrahedral sulfate ion. [4][5][6][7][8][9][10][11][12][13][14] In classical transition-metal coordination, the chelate effect has been extensively studied as a major contributor to enhanced stabilities in transition metal complexes. [15][16][17][18][19][20][21] In anion coordination, the chelate effect also plays an important role.…”
mentioning
confidence: 99%